Using follicle stimulating hormone (FSH) for superovulation in buffalo - Polmer Situmorang (Jurnal Ilmu Ternak dan Veteriner, 2006)
Studies of superovulation have been carried out in buffaloes and the progress has been achieved but the number of embryo collected was still small. Two studies were conducted to evaluate the use Follicle Stimulating Hormone (FSH) for superovulation in buffalo. First study, fifteen buffaloes were randomly divided into 3 groups of five buffaloes of each group and superovulated using three type of FSH (FSH-P; FSC-China and Folltropin). Hormones were given twice a day for 4 days in decreasing doses methods. First injection initiated on day 10 of estrus cycle, followed by prostaglandin on day 12 than artificially inseminated (AI) two days later. Recovery of embryo was conducted un-surgically method by flushing uterus horn on day 6 after AI. Second study, 10 buffaloes were randomly divided into 2 groups of each five buffaloes First group was superovulated with FSH followed methodology in the first study (control group) and second group were given a prime FSH on day 1 of estrus cycle before superovulation (treatment group). After 3 months the superovulation was repeated in the reverse condition where the control become treatment and the treatment become a control group. The type of FSH did not significantly affect the superovulatory response. The mean total corpus luteum (TCL), total number of embryo (TNE) and total number of viable embryo (TVE) were 6.8, 3.3 and 2.2,  6.2, 3.0 and  2.1 and  7.2, 3.6 and  2.4 for FSH-P, FSH China and Folltropin respectively. A single injection of FSH significantly increased (P<0.05) the number of embryo collected. The mean TCL, TNE and TVE were 6.9, 2.8 and 2.1 and 8.2, 3.3 and 2.5 for control and treatments respectively. The peak progesterone level was significantly higher (P<0.05) in treatment group (6.8 ng/ml) than those in control (5.6 ng/ml). Repeated the superovulation after 3 months did not significantly affect the number of embryo collected. In conclusion, superovulation in buffaloes can be performed using a types of FSH and prime injection of FSH on day 1 of estrus cycle increase the number of embryo recovered. The superovulation can be conducted after 3 months. Key Words: FSH, Superovulation, Embryo